Management of Blended Learning and Digital Skills and Their Influence on the Learning Independence of Vocational Students - Patabang, Apriani; Mesta Limbong; Tarsicius Sunaryo (Universitas Pendidikan Ganesha, 2023)
Changes in the implementation of learning due to the Covid 19 pandemic impact learning methods, so teachers and students must be able to adapt to online learning policies. This study analyzed the effect of blended learning management and digital skills on student learning independence. This type of research is ex post facto research, namely comparative causal research. The population in this study were all vocational school teachers, with a total sample of 103 respondents. Data collection was carried out by distributing instruments in the form of questionnaires. Data analysis techniques are correlation and regression. The results of the data analysis show that the model, namely the teacher's blended learning management and digital skills, can explain variations in student learning independence. The R square value of 0.589 indicates that the model, namely X1 and X2, can explain the variation in Y of 58.9%. Based on these results, teachers must implement blended learning management optimally and be supported by developing students' digital skills to increase learning independence. The implications of this research can be used as input, reference, and discourse on students' independent learning about blended learning management and digital skills.